Endometrial proteomic signature in recurrent implantation failure - Dogan, M.; Demiral, I.; Akgun, E.; Ulgen, E.; Gurel, B.; Sahin, B.; Aytan, A. Nehir; Ozgor, B. Yuksel; Baykal, A. T.; Sezerman, U.; Bastu, E.; Buyru, F. (OXFORD UNIV PRESS, 2018)
34th Annual Meeting of the European-Society-of-Human-Reproduction-and-Embryology (ESHRE), Barcelona, SPAIN, JUN 01-04, 2018